Amplifying fluorescence signal contrast of aptamer-modified microspheres inspired by whispering-gallery mode lasing. Issue 37 (6th June 2018) - Kim, Sooyeon; Kuroda, Ayaka; Fujitsuka, Mamoru; Majima, Tetsuro
Abstract : We propose a new sensor design that maximizes fluorescence contrast, inspired by whispering-gallery mode lasing (WGM). Abstract : We propose a new sensor design that maximizes fluorescence contrast, inspired by whispering-gallery mode lasing (WGM). Aptamer-modified glass microspheres ( cf. 1–38 μm) and thrombin are used as a model sensory cavity and target protein, respectively. Two types of microsphere are prepared to compare fluorescence contrast: turn-on and turn-off types by using fluorophore-labeled target protein and fluorophore-labeled DNA duplex with thrombin-binding aptamer (TBA), respectively. For the turn-on type, a fluorescence increase was detected in the presence of 100 nM thrombin, but signal amplification upon excitation power did not occur. As for the turn-off type, in the absence of thrombin, fluorophores are densely populated around the microsphere, leading to fluorescence confinement and intensity amplification upon increasing the pump intensity. By adding thrombin, a complementary strand of TBA is dissociated from the microsphere, and the G-quadruplex structure of the thrombin aptamer recognizes and binds to thrombin. As the fluorophore density around the microsphere decreases, fluorescence amplification based on WGM resonance is halted, resulting in 29-fold enhanced contrast under increased excitation power.